Finite element study on axially static loading test and bidirectional static osterberg cell pile load testing - Aygül, Tuğba. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
There are several methods used in the design of bored piles. Mathematical modeling of the pile and soil parameters, provide various formulas and theories for ultimate bearing capacity and settlement calculations of a pile. Many factors, including construction methods and real site conditions affect the vertical load capacity, so such model based analyses seldom give fully reliable results. From that reason, pile load tests are the most fundamental part of pile foundation design. Although many pile tests have been constructed in all kinds of engineering projects, it is unclear what difference arises from newer test methods such as the O-cell test. In this thesis, the finite element method (FEM) was used to carry out the research. The commercial finite element code PLAXIS was used for the numerical simulation of pile load test in the following manner. The thesis focuses on some particular interest which is to compare the allowable capacity and displacement values of several test results with each other and also with the numerical simulation of five different case studies. Furthermore, O-cell test is compared with static pile load test and equivalency and discrepancy of the test results between the two types of pile load test are demonstrated and analyzed. It is concluded that O-cell test result can provide not only the same soil-pile interaction information as conventional headdown static loading test, but also allow for separate determination of the shaft resistance and end bearing components. However, the equivalent head down load-movement curve of the O-cell test simulated by PLAXIS 8 gives a slightly stiffer load-movement response and slightly higher ultimate capacity than those of conventional test.
Keywords: Bridges -- Foundations and piers -- Testing.; Piling (Civil engineering) -- Testing.; Bridges -- Live loads -- Testing.